Effect of Perioperative Nicorandil on Myocardial Protection in Patients Undergoing Cardiac Surgery with Cardiopulmonary Bypass, a Retrospective Study - Chen Y; Liu Y; Lv H; Li Q; Shen J; Chen W; Shi J; Zhou C (Dove Medical Press, 2024)
Yuye Chen,1 Yue Liu,2 Hong Lv,1 Qian Li,1 Jingjia Shen,1 Weiyun Chen,2 Jia Shi,1 Chenghui Zhou3 1Department of Anesthesiology, Fuwai Hospital, Chinese Academy of Medical Sciences&Peking Union Medical College/National Center for Cardiovascular Diseases, Beijing, 100037, People's Republic of China; 2Department of Anesthesiology, Peking Union Medical College Hospital, Beijing, 100730, People's Republic of China; 3Center for Anesthesiology, Beijing Anzhen Hospital, Capital Medical University, Beijing, 100029, People's Republic of ChinaCorrespondence: Chenghui Zhou, Center for Anesthesiology, Beijing Anzhen Hospital, Capital Medical University, No. 2 Anzhen Road, Chaoyang District, Beijing, 100029, People's Republic of China, Tel +86-137-1889-4919, Email chenghuizhou@vip.163.com Jia Shi, Department of Anesthesiology, Fuwai Hospital, Chinese Academy of Medical Sciences&Peking Union Medical College/National Center for Cardiovascular Diseases, No. 167 North Lishi Road, Xicheng District, Beijing, 100037, People's Republic of China, Email shijia@fuwai.comBackground: The potential myocardial protective effect of nicorandil (NICD) in patients undergoing percutaneous coronary intervention has been established. However, its efficacy in the context of cardiac surgery remains controversial. The present study aimed to evaluate the myocardial protective effect of perioperative NICD use in patients undergoing cardiac surgery with cardiopulmonary bypass (CPB).Methods: We retrospectively gathered data from patients undergoing cardiac bypass surgery between 12/2018 and 04/2021 in Fuwai Hospital. Subsequently, the patients were divided into two groups, NICD group and non-nicorandil (non-NICD) group. A 1, 3 propensity score matching (PSM) was conducted. The primary outcome was the incidence of myocardial injury. The secondary outcomes included the mechanical ventilation (MV) duration, intensive care unit (ICU) length of stay (LOS), hospital LOS, duration of chest drainage, the drainage volume, the total cost, the incidence of acute kidney injury (AKI), and the incidence of acute liver injury (ALI). Subsequently, we divided the entire population into two distinct subgroups based on their administration of NICD, and performed a comprehensive subgroup analysis.Results: A total of 2406 patients were ultimately included in the study. After PSM, 250 patients in NICD group and 750 patients in non-NICD group were included in the analysis. Perioperative NICD reduced the incidence of myocardial injury (47.2% versus 38.8%, P=0.025). Our subgroup analysis revealed that preoperative NICD administration not only provided myocardial protection benefits (45.7% vs 35.8%, OR 0.66, 95% CI [0.45- 0.97], P=0.041), but also demonstrated statistically significant reduction in ALI, the ICU and hospital LOS, and the duration of chest drainage (all P< 0.05).Conclusion: The perioperative NICD administration may confer myocardial protection in patients undergoing cardiac surgery with CPB. Furthermore, the preoperative utilization of NICD has the potential to mitigate the incidence of postoperative ALI, a reduction in the ICU and hospital LOS, and the duration of chest drainage.Keywords: nicorandil, cardiopulmonary bypass, perioperative myocardial injury, acute kidney injury, acute liver injury